Synthesis and spectral characterization of macrocyclic Schiff base by reaction of 2,6-diaminopyridine and 1,4-bis(2-carboxyaldehydephenoxy)butane and its CuII, NiII, PbII, CoIII and LaIII complexes - Ilhan, Salih; Temel, Hamdi; Ziyadanogullari, Recep; Sekerci, Memet (Springer, 2007)
A new macrocyclic ligand, 1,3,5-triaza-2,4:7,8:15,16-tribenzo-9,15-dioxacycloheptadeca-1,5-diene (L) was synthesized by reaction of 2,6-diaminopyridine with 1,4-bis(2-carboxyaldehydephenoxy)butane. Then, its Cu-II, Ni-II, Pb-II,and Co-III and La-III complexes were synthesized by the template effect by reaction of 2,6-diaminopyridine and 1,4-bis(2-carboxyaldehydephenoxy)butane and Cu(NO3)(2)center dot 3H(2)O, Ni(NO3)(2) center dot 6H(2)O, Pb(NO3)(2), Co(NO3)(2) center dot 6H(2)O, La(NO3)(3) center dot 6H(2)O, respectively. The ligand and its metal complexes were characterized by elemental analysis, IR, H-1- and C-13-n.m.r., UV-vis spectra, magnetic susceptibility, thermal gravimetric analysis, conductivity measurements and mass spectra. All complexes are diamagnetic and the Cu-II complex is binuclear. The Co-II complex was oxidised to Co-III.
Keywords: X-Ray; Lanthanide(Iii) Complexes; Copper(Ii) Complexes; Nickel(Ii) Complexes; Template Synthesis; Crystal-Structure; Ligand; Coordination; Tetradentate; Mononuclear